2015
DOI: 10.1039/c4ra13972k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclay-reinforced electrospun chitosan/PVA nanocomposite nanofibers for biomedical applications

Abstract: Chitosan/PVA/nanoclay nanocomposite nanofibers have been prepared successfully by electrospinning. Bead-free morphology was achieved for the nanofibrous mats and the nanoclays were incorporated and distributed uniformly inside the nanofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 25 publications
10
96
1
Order By: Relevance
“…The composite mechanical properties and thermal stability have been shown to increase with chitosan oligosaccharide and montmorillonite contents [58]. XRD results confirmed that these improvements were related to the MMT exfoliation and strong interaction between the PVA/chitosan blend and MMT [58,[60][61][62].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The composite mechanical properties and thermal stability have been shown to increase with chitosan oligosaccharide and montmorillonite contents [58]. XRD results confirmed that these improvements were related to the MMT exfoliation and strong interaction between the PVA/chitosan blend and MMT [58,[60][61][62].…”
Section: Introductionmentioning
confidence: 63%
“…These results revealed that chitosan is miscible in PVA for weight fractions of chitosan w Ch >0.2 [53]. Characterization of films made of chitosan with poly(vinyl alcohol) and montmorillonite has been reported [58][59][60][61][62]. The composite mechanical properties and thermal stability have been shown to increase with chitosan oligosaccharide and montmorillonite contents [58].…”
Section: Introductionmentioning
confidence: 88%
“…According to the reference, it was reported as an endothermic peak derived from chitosan (Koosha et al, 2015). Chitosan peaks at around 60-80 had a tendency to shift slightly as the proportion of oleic acid increases, which is seen as an effect between the chitosan and oleic acid (Ruhi et al, 2015).…”
Section: Dsc Thermograms Of Cbfg-filmsmentioning
confidence: 99%
“…These blends can be converted into variety of forms using different methods like electrospinning, nanofiber drawing, template synthesis, layer-by-layer deposition and self-assembling. Polymer blends and composites is an effective method to achieve new obligations for different properties of the materials [1,2]. Currently, electrospinning of blend polymers are inspected as promising materials for biomedical and industrial applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%